Intensive drying of an infinite plate - Tripathi G.; Shukla K.N.; Pandey R.N. (My University, 2025)
Kinetics of drying mechanism is studied for the capillary porous body. Local values of temperature, moisture content and pressure are evaluated analytically under the most general type of boundary conditions. The novelty of the work lies in consideration of the generalised surface conditions which includes all types of the interaction law between the moist body and the surrounding. Analytical result indicates that the process is intensified by the filtrational drying. © 1977.